Development, explanation, and presentation of the Physical Literacy Interventions Reporting Template (PLIRT) - Carl, Johannes; Barratt, Jaime; Arbour-Nicitopoulos, Kelly; Barnett, Lisa M; Dudley, Dean A; Holler, Peter; Keegan, Richard; Kwan, Matthew; Scurati, Raffaele; Kim-Wai Sum, Raymond; Wainwright, Nalda; Cairney, John (International Journal of Behavioral Nutrition and Physical Activity, 2023)
Background The physical literacy (PL) concept integrates different personal (e.g., physical, cognitive, psychological/affective, social) determinants of physical activity and has received growing attention recently. Although practical efforts increasingly adopt PL as a guiding concept, latest evidence has shown that PL interventions often lack specification of important theoretical foundations and basic delivery information. Therefore, the goal of the present study was to develop an expert-based template that supports researchers and practitioners in planning and reporting PL interventions. Methods The development process was informed by Moher et al.’s guidance for the development of research reporting guidelines. We composed a group of ten distinguished experts on PL. In two face-to-face meetings, the group first discussed a literature-driven draft of reporting items. In the second stage, the experts anonymously voted and commented on the items in two rounds (each leading to revisions) until consensus was reached. Results The panel recommended that stakeholders of PL initiatives should tightly interlock interventional aspects with PL theory while ensuring consistency throughout all stages of intervention development. The Physical Literacy Interventions Reporting Template (PLIRT) encompasses a total of 14 items (two additional items for mixed-methods studies) in six different sections: title (one item), background and definition (three items), assessment (one item each for quantitative and qualitative studies), design and content (five items), evaluation (one item plus one item each for quantitative and qualitative studies), discussion and conclusion (two items). Conclusion The PLIRT was designed to facilitate improved transparency and interpretability in reports on PL interventions. The template has the potential to close gaps between theory and practice, thereby contributing to more holistic interventions for the fields of physical education, sport, and healt